System Development Methodology For Accounting Infoemation System - Devi Dwi Putri; Yusri Hazmi*; Fitri Yana; Reka Nabella; Yuni Saputri (Pt. Anagata Sembagi Education, 2024)
This study discusses the importance of selecting an appropriate information system development method before starting the development process to ensure the creation of a system that meets expectations. Although there are many methodologies or models for software development, confusion often arises when choosing the most suitable one based on specific situations or environments. The article also outlines the basic concepts of systems, accounting information systems, and the stages of system analysis, including proposal preparation, system analysis implementation, and the preparation of system analysis reports. The research methodology used is library research, which involves studying literature and analyzing various written information sources. The findings highlight the importance of written documentation at each stage of system development to effectively communicate plans and findings to information users, as well as the significance of employing effective information-gathering techniques during system analysis. Therefore, selecting the right method and maintaining thorough documentation are crucial to successfully developing an information system that meets user needs and supports organizational goals.